Evaluation of the performance of SARS‐CoV‐2 antibody assays for a longitudinal populationbased study of COVID‐19 spread in St. Petersburg, Russia. Issue 10 (12th June 2021) - Barchuk, Anton; Shirokov, Daniil; Sergeeva, Mariia; Tursunzade, Rustam; Dudkina, Olga; Tychkova, Varvara; Barabanova, Lubov; Skougarevskiy, Dmitriy; Danilenko, Daria
Abstract: Geographical variation in severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) spread requires seroprevalence studies based on local tests, but robust validation is needed. We summarize an evaluation of antibody tests used in a serological study of SARS‐CoV‐2 in Saint Petersburg, Russia. We validated three different antibody assays: chemiluminescent microparticle immunoassay (CMIA) Abbott Architect SARS‐CoV‐2 immunoglobulin G (IgG), enzyme linked immunosorbent assay (ELISA) CoronaPass total antibodies test, and ELISA SARS‐CoV‐2‐IgG‐EIA‐BEST. Clinical sensitivity was estimated with the SARS‐CoV‐2 polymerase chain reaction (PCR) test as the gold standard using manufacturer recommended cutoff. Specificity was estimated using prepandemic sera samples. The median time between positive PCR test results and antibody tests was 21 weeks. Measures of concordance were calculated against the microneutralization test (MNA).Sensitivity was equal to 91.1% (95% confidence intervbal [CI]: 78.8–97.5), 90% (95% CI: 76.4–96.4), and 63.1% (95% CI [50.2–74.7]) for ELISA Coronapass, ELISA VectorBest, and CMIA Abbott, respectively. Specificity was equal to 100% for all the tests. Comparison of receiver operating characteristics has shown lower AUC for CMIA Abbott. The cutoff SC/O ratio of 0.28 for CMIA Abbott resulted in a sensitivity of 80% at the same level of specificity. Less than 33% of the participants with positive antibody test results had neutralizing antibodies in titers 1:80 and above. Antibody assays results and MNA correlated moderately. This study encourages the use of local antibody tests and sets the reference for seroprevalence correction. Available tests' sensitivity allows detecting antibodies within the majority of PCR positive individuals. The Abbott assay sensitivity can be improved by incorporating a new cutoff. Manufacturers' test characteristics may introduce bias into the study results. Highlights: 1) This report is the first diagnostic performance study of antibody assays used in the representative population‐based serological study of SARS‐CoV‐2 in St. Petersburg, Russia. 2) The sensitivity for two local assays was equal to 91.1% (95%CI: 78.8‐97.5) and 89.1% (95%CI: 76.4‐96.4), CMIA Abbott's sensitivity was equal to 63.1% (95%CI 50.2‐74.7)), with 100% specificity for all the tests. 3) Moving the S/CO ratio from Abbott assays from manufacturers recommended 1.4 to 0.28 improved sensitivity from 63% to 80%, without loss in specificity. 4) Less than a third of samples positive for binding antibodies were also positive in the virus neutralization test (with 1:80 titer as a threshold) in the population‐based sample.